Phylogeny and phylogeography of atlantic islands' Columba species - Dourado, Ana Catarina Gonçalves (2011)
Tese de mestrado. Biologia (Biologia Humana e Ambiente). Universidade de Lisboa, Faculdade de Ciências, 2011